Outcome of nonoperative treatment for hip fractures in elderly patients: A systematic review of recent literature - Seung-Ju Kim (Journal of Orthopaedic Surgery, 2020)
Many studies have shown that surgical management still leads to the best outcomes in elderly patients with hip fractures, with some studies showing non-inferiority of nonsurgical management as compared to surgery in fragility fractures. Evidence-based guidelines on whether to operate on these patients are lacking. A systematic literature search was conducted regarding outcomes of nonoperatively treated hip fractures in elderly patients with various comorbidities. A structured literature review of multiple databases (PubMed, Web of Science, EMBASE, and Cochrane library) referenced articles from 2000 to 2020. A total of 596 patients from 11 published studies were identified. Mean age was 83.3 years. Overall 328 (69.7%) complications occurred in 470 patients with nonsurgical treatment. Pneumonia and urinary tract infections were the most common complications which occurred in 53 (16.1%) and 46 (14.0%) patients, respectively. Hip fracture patients who were treated nonoperatively had a higher in-hospital (17.1% vs. 4.4%; p < 0.001), 30-day (31.4% vs. 10.2%; p < 0.001), and 1-year (48.5% vs. 19.9%; p < 0.001) mortality compared to a matched group of operatively treated patients ( n = 1464). Of the 110 patients whose reported cause of death was nonoperative care, 44 (40%) was due to pneumonia. Patients with nonoperative treatment following hip fracture were associated with substantially higher complication and mortality compared with patients who were treated operatively. Our study will help health-care providers and caregivers to enable more informed decision-making for families and patients confronted with a hip fracture.